Pengaruh Kecerdasan Emosional dan Kecerdasan Spiritual Terhadap Prestasi Belajar Pendidikan Agama Islam Dan Budi Pekerti Peserta Didik Di SD Negeri Kecamatan Pamboang - Ramadani, Ayuniar; Saprin,; Ulfiani Rahman,; Wahyuni Ismail, (Tasamuh: Jurnal Studi Islam, 2024)
The impact of spiritual and emotional intelligence on students' learning outcomes in Islamic Religious Education and Budi Pekerti in SD Negeri Pamboang District is examined in this study. This kind of study is categorized as quantitative research with Ex Post Facto paradigm. A questionnaire was utilized for data collection, and descriptive and inferential statistics, together with partial and multiple regression analysis for hypothesis testing, were employed for analysis. The study's findings suggest that: 1) The Pamboang sub-district's primary school kids' learning success demonstrates the greatest proportion in the range of 81-79, with a frequency of 48 and a percentage of 31%. That is, 48 students received a score between 79 and 81; 2) With a coefficient of determination of 54%, emotional intelligence has an impact on students' learning success in the PAI and Budi Pekerti topics in SD Negeri Pamboang District. This indicates that emotional intelligence has a significant enough impact on pupils' academic success; 3) With a determination coefficient of 27,8%, spiritual intelligence has an impact on students' learning success in the PAI and Budi Pekerti topics in SD Negeri Pamboang District. This indicates that spiritual intelligence has a significant impact on students' learning outcomes; 4) Students' learning outcomes in PAI and Budi Pekerti topics are influenced by both spiritual and emotional intelligence, with a 61% coefficient of determination. This indicates that spiritual and emotional intelligences have a significant enough impact on students' learning outcomes.